Class and Social Structure in Hungarian Sociology. (August 2015) - Gagyi, Ágnes; Éber, Márk Áron
The article follows changes in the paradigms and institutional context of Hungarian sociology of social structure, as formed by Hungary's double dependence on Soviet and Western cores throughout the second part of the twentieth century. It demonstrates that as a result of those changes, the concept of class has been absent from the sociology of social structure from the early 1970s on. Thinking towards a possible reconstruction of twentieth-century Hungarian social formation in a class-sensitive perspective embedded in the dynamics of the capitalist world system, we point at a typical effect of global hierarchies on the description of local social structure: the tendency to identify a "double structure" in local society. This gesture places various characteristics of local society on two different ontological levels—for example, Western versus Eastern, future versus past. We argue that in order to conceive of local social formation as part of an integrated global history, this internalized effect of global hierarchies needs to be transcended.